1996
DOI: 10.1046/j.1365-313x.1996.09040559.x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid potentiates defence gene expression in tissue exhibiting acquired resistance to pathogen attack

Abstract: Salicylic acid (SA) is absolutely required for establishment of acquired resistance in non‐infected tissues following localized challenge of other leaves with a necrotizing pathogen. Although not directly responsive to SA, or induced systemically following pathogen challenge, the expression of defence gene promoter fusions AoPR1—GUS and PAL‐3—GUS after wounding or pathogen challenge could be enhanced by pre‐treating tobacco plants hydroponically with SA, a phenomenon designated ‘potentiation’. Potentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(123 citation statements)
references
References 0 publications
8
114
0
1
Order By: Relevance
“…Because it is thought that 2,6-dichloroisonicotinic acid acts at the same point as or downstream of SA in this pathway (Delaney et al, 1995), one conclusion is that these mutants define steps in a feedback loop operating to interpret SA-dependent signals. These genetic results are consistent with other results implicating a feedback role for SA during the defense response (Kauss et al, 1992;Kauss and Jeblick, 1995;Mauch-Mani and Slusarenko, 1996;Mur et al, 1996; see also Ryals et al, 1996, in this issue). It will also be informative to combine the cell death control mutants with other mutants required for R gene function, such as ndr (Century et al, 1995), whose position in the scheme shown in Figure 2 is tentative.…”
Section: Undoing Death: Genetic Exploitation Of Cell Death Control Musupporting
confidence: 91%
“…Because it is thought that 2,6-dichloroisonicotinic acid acts at the same point as or downstream of SA in this pathway (Delaney et al, 1995), one conclusion is that these mutants define steps in a feedback loop operating to interpret SA-dependent signals. These genetic results are consistent with other results implicating a feedback role for SA during the defense response (Kauss et al, 1992;Kauss and Jeblick, 1995;Mauch-Mani and Slusarenko, 1996;Mur et al, 1996; see also Ryals et al, 1996, in this issue). It will also be informative to combine the cell death control mutants with other mutants required for R gene function, such as ndr (Century et al, 1995), whose position in the scheme shown in Figure 2 is tentative.…”
Section: Undoing Death: Genetic Exploitation Of Cell Death Control Musupporting
confidence: 91%
“…A plausible explanation is that ISR-expressing plants are potentiated for the expression of JA-inducible, defense-related genes, leading to a faster and greater gene activation after infection with a challenging pathogen. Potentiation of defense-related gene activation has been demonstrated for SA-inducible PR genes in SAR-expressing tobacco [33] and Arabidopsis plants [52]. Recently, we demonstrated that the expression of the JA-inducible Atvsp gene is potentiated in ISRexpressing plants [52], leading to a higher Atvsp transcript accumulation after challenge inoculation.…”
Section: Discussionmentioning
confidence: 91%
“…syringae system, PAL expression may be amplified in vascular tissue by a product of the phenylpropanoid pathway. For example, SA has been reported to potentiate the expression of PAL and other defense-related genes, allowing higher levels of expression in response to elicitors (Mur et al, 1996;Shirasu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%